Numerical Simulation for Activation Energy Impact on Darcy-Forchheimer Flow of Casson Fluid Suspended with Nano Particles over a Stretching Cylinder - Sarve, Deepak; Kumar Gaur, Pradip; Sharma, Vishnu Kumar (Science & Technology Asia, 2021)
This present work concentrates on the influence of energy of activation on Darcy- Forchheimer flow of Casson fluid with nano particles. The formulation of the mathematical model is done by considering Casson fluid with TiO2and Cu as nanoparticles dispersed in the base Ethylene glycol. The governing equations are reduced by using standard similarity variables and boundary conditions to obtain ODE’s. The numerical solution is approximated by using Rung-Kutta Fehlberg’s5th order technique. The influence of numerous pertinent physical parameters on the velocity profile and the thermal profile are plotted by using BVP4C condition in MATLAB software.